Investigation Effects Digital Literacy on Primary Student Attitude in Indonesia - Yasa, Arnelia Dwi; Rahayu, Sri; Handayanto, Supriyono Koes; Ekawati, Ratna (Universitas Pendidikan Ganesha, 2024)
The rapid development of technology has brought significant changes in education at all school levels. To improve the quality of learning, the utilization of Information and Communication Technology (ICT) is becoming increasingly important. This study aims to evaluate students' digital literacy profile and investigate the impact of digital literacy dimensions on students' attitudes towards using ICT for learning. This study utilized mixed methods of the sequential explanatory type, with data collected through a survey of 415 students in Malang, Indonesia. Data was collected through a questionnaire with 17 attributes representing attitude and digital literacy variables. Data analysis included descriptive statistics to assess the level of attitude and digital literacy and regression analysis to examine the influence of digital literacy on students' attitudes in utilizing ICT. In addition, semi-structured interviews with twelve participants were conducted to confirm the findings regarding the level of attitudes and digital literacy. Results from the survey and interviews showed that students' attitudes toward ICT utilization received the highest score, followed by the social-emotional, technical, and cognitive dimensions. Regression test results revealed that technical, social-emotional, and cognitive variables significantly influenced students' attitudes toward ICT.